(untitled) (Plant Bulletin, 2024)
Red spider mite, Tetranychus urticae Koch, causes severe damage to economically important crops, fruits, vegetables, ornamentals etc. Management of red spider mite largely depends on chemicals. Application of insecticides may cause massive outbreaks of mite population. Sublethal effects of imidacloprid, thiamethoxam and acetamiprid doses were investigated on life-table parameters of red spider mite. All neonicotinoids revealed significant effects on life characteristics i.e. development duration and fecundity of red spider mite. Mites treated with imidacloprid, thiamethoxam and acetamiprid significantly reduced the net reproductive rate (Ro). No significant difference in finite rates of increase (λ) was observed among the treatments. Imidacloprid reduces the egg duration and mean generation time (T). Emerged adult longevity was shorter when exposed to insecticides. The total adult longevity was significantly reduced by the insecticides in comparison with the control. Highest mean generation time was observed in acetamiprid treated mites. The results suggested that sublethal effects of tested insecticides affected the biological parameters of red spider mite.